Twitter, opinião pública e a guerra comercial com a China: um estudo sobre a construção da agenda midiática por Donald Trump (2017 – 2021) - Mendes, Andressa Gabrielly de Lacerda (2021)
In January of 2017 Donald Trump was elected the President of the United States of America after a politically polarized electoral campaign, especially in the century of information and network Society. It is in this context that this work aims to explain how Donald Trump was a builder of the media agenda on the trade war with China issue during his term (2017 – 2021). The hypothesis is that the media debate construction on the trade war was made by the use of Twitter by the ex-president. It is understood that the concern with China was incorporated as a political communication strategy by the Trump government and, consequently, influenced the U.S. public opinion on the subject. Therefore, the concepts of media, public opinion, political communication, Trumpism, and others will be mobilized. It will also be presented a historical retrospective on how the trade relationship between the United States and China happened; a presentation of opinion polls carried out by Gallup and the Pew Research Center; quantitative and qualitative surveys of the Trump Twitter Archive and Internet Archive’s Television News database; and the fulfillment of a case study on May 10TH , 2019, when Donald Trump most tweeted about the trade war with China.